Learning to Read in the Digital Age: From Reading Texts to Hacking Codes. - CITTON, YVES (PMLA: Publications of the Modern Language Association of America, 2015)
The article examines the aspects of learning and reading in digital age in terms of reading texts and hacking codes. Topics discussed include theories of interpretation, the Common Core State Standards Initiative that details what high school students should know about English language and reprocessing of data such as texts, slogans and keywords.